2017
DOI: 10.3904/kjim.2016.118
|View full text |Cite
|
Sign up to set email alerts
|

Maximal pericoronary adipose tissue thickness is associated with hypertension in nonobese patients with acute or chronic illness

Abstract: Background/AimsRecent studies have shown an association of epicardial fat thickness with diabetes and hypertension (HTN) in asymptomatic populations. However, there is lack of information as to whether there is similar association between pericoronary adipose tissue (PAT) and HTN in the patients who have acute or chronic illness.MethodsThis study included 214 nonobese patients hospitalized with acute or chronic noncardiogenic illness. PAT thicknesses were measured from fat tissues surrounding left and right co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Some previous studies conducted by other authors confirm the increase in size of EAT depots among the patients with EH [18,19,31,32,33,34,35]. The difference between our study and the majority of previous studies is that along with EAT thickness measurements we have also measured EAT volume.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Some previous studies conducted by other authors confirm the increase in size of EAT depots among the patients with EH [18,19,31,32,33,34,35]. The difference between our study and the majority of previous studies is that along with EAT thickness measurements we have also measured EAT volume.…”
Section: Discussioncontrasting
confidence: 52%
“…Along with EH occurrence disparities, diverging results regarding the correlation between the size of EAT depots and blood pressure are presented in the literature [19,26]. We have found no studies where EAT depots would be assessed with respect to the grade of hypertension that describes the state of a patient more accurately than momentary blood pressure measurements.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Many studies agree that the amount of EAT is higher in hypertensive adult patients [ 16 , 26 , 27 , 28 , 29 ]. There are fewer studies which propose this link in children and adolescents [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Özdil et al EAT thickness measured by echocardiography was an independent predictor of new diagnosis of hypertension [ 34 ]. Chang et al performed a study on 214 non-obese patients hospitalized with acute or chronic non-cardiogenic illness and found that EAT thickness was independently correlated with hypertension, age, and BMI [ 35 ]. Moreover, in another study on 80 patients who were diagnosed with hypertension EAT thickness showed a significant correlation with 24-h SBP ( r = 0.434, p < 0.001) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%